Role of Advanced Cardiac Magnetic Resonance Imaging in Atypical Cardiomyopathies such as Stress-Induced Cardiomyopathie and Left-Ventricular Non-Compaction Cardiomyopathy - Strohm, Oliver; Shehab, Abdullah; Qureshi, Anwer (IntechOpen, 2012)
None